Mučenje - nerešljivost problema? - Simoniti, Iztok (Teorija in praksa, 2007)
The author discusses extreme, yet real cases indicating the invalidity of the assertion that, for rational people, torture is unacceptable under any condition, regardless of the circumstances. Since human beings are incapable of organizing free societies without violence, torture remains an unsolvable problem. So far we have been unable to resolve it in any other way than by prohibiting torture by law, yet simultaneously practising it in concealment. Therefore a constant discussion of such a state of affairs is required paralleled by the insistence on national and international legislation (entirecorpus of international humanitarian law, including the International Criminal Court) bearing it in mind that the ideal of justice can only be approached, when the spirit of the law is supplemented by the wisdom of judges.
Keywords: Mučenje; Torture; International law; Mednarodno pravo; Morala; morality; Morals; State; Država; society; družba; družbeno vedenje; nasilje; pravna odgovornost